Association between proton-pump inhibitors and the risk of gastric cancer: a systematic review with meta-analysis. (October 2021) - Segna, Daniel; Brusselaers, Nele; Glaus, Damian; Krupka, Niklas; Misselwitz, Benjamin
Introduction: The use of proton-pump inhibitors (PPI) may be associated with an increased risk of gastric cancer (GC). Objective: To review and meta-analyse available literature investigating the association between PPI use and GC risk. Methods: Two independent reviewers systematically searched Ovid MEDLINE, EMBASE, and Cochrane Library (inception to July 2020) for case-control and cohort studies assessing the association between PPI use and GC according to a predefined protocol in PROSPERO (CRD42018102536). Reviewers independently assessed study quality, extracted data, and meta-analysed available and newly calculated odds ratios (ORs) using a random-effects model, and stratified for GC site (cardia versus non-cardia) and PPI duration (<1 year, 1–3 years, >3 years). Results: We screened 2, 396 records and included five retrospective cohort and eight case-control studies comprising 1, 662, 881 individuals in our meta-analysis. In random-effect models, we found an increased GC risk in PPI users [OR: 1.94, 95% confidence interval (95% CI): 1.47–2.56] with high statistical heterogeneity ( I 2  = 82%) and overall moderate risk of bias. Stratified analyses indicated a significant risk increase in non-cardia (OR: 2.20, 95% CI: 1.44–3.36, I 2  = 77%) with a similar non-significant trend in cardia regions (OR: 1.77, 95% CI: 0.72–4.36, I 2  = 66%). There was no GC increase with longer durations of PPI exposure (<1 year: OR: 2.29, 95% CI: 2.13–2.47, I 2  = 0%; 1–3 years: OR: 1.46, 95% CI: 0.53–4.01, I 2  = 35%; >3 years: OR: 2.08, 95% CI: 0.56–7.77, I 2  = 61%). Conclusion: We found a twofold increased GC risk among PPI users, but this association does not confirm causation and studies are highly heterogeneous. PPI should only be prescribed when strictly indicated.